2023
DOI: 10.3390/cells12141853
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Growth Ameliorates Cardiac Dysfunction

Abstract: Heart failure and cancer are the deadliest diseases worldwide. Murine models for cardiac remodeling and heart failure demonstrate that cardiac dysfunction promotes cancer progression and metastasis spread. Yet, no information is available on whether and how tumor progression affects cardiac remodeling. Here, we examined cardiac remodeling following transverse aortic constriction (TAC) in the presence or absence of proliferating cancer cells. We show that tumor-bearing mice, of two different cancer cell lines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…One such disease is DMD, an X-linked genetic disease, that involves fibrosis in cardiac, diaphragm, and skeletal muscles [20]. While recent studies have shown that injecting two aggressive murine cancers (PyMT and LLC cell line) reduces cardiac hypertrophy and fibrosis and enhances cardiac function in multiple mouse models [2,3,5], it was not addressed whether the aggressiveness and nature of cancer types impacted this improvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One such disease is DMD, an X-linked genetic disease, that involves fibrosis in cardiac, diaphragm, and skeletal muscles [20]. While recent studies have shown that injecting two aggressive murine cancers (PyMT and LLC cell line) reduces cardiac hypertrophy and fibrosis and enhances cardiac function in multiple mouse models [2,3,5], it was not addressed whether the aggressiveness and nature of cancer types impacted this improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrotic diseases contribute to approximately half of the mortality rate in developed countries and present an unresolved clinical need [1]. In recent studies, we demonstrated that injecting two different murine cancer cell lines representing breast and lung cancer resulted in the amelioration of cardiac dysfunction, reduced cardiac hypertrophy, and lower cardiac fibrosis, in a pressure overload [2] and transgenic mouse model for heart hypertrophy [3]. To further establish the suppression of fibrosis in other organs as well, we used the MDX mouse model for Duchenne muscular dystrophy (DMD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the effect of HF on cancer progression is well defined, less is known about the opposite direction, namely, tumors’ effect on cardiac dysfunction. A case in point is a recently published study that demonstrated that cancer cell growth of either breast or lung cancer ameliorates cardiac dysfunction and suppresses remodeling processes following pressure overload induced by Transverse Aortic Constriction (TAC) surgery [ 12 ]. Tumor-bearing mice showed an enhanced cardiac contractility function, and a decrease in cardiac hypertrophy and fibrosis levels.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-bearing mice showed an enhanced cardiac contractility function, and a decrease in cardiac hypertrophy and fibrosis levels. This phenotype was shown to be mediated by the involvement of the innate immune system and more specifically an M2 macrophage switch in the heart [ 12 , 13 ]. The TAC model involves a major surgical intervention that may have side effects.…”
Section: Introductionmentioning
confidence: 99%